Transfusion-Transmitted Malaria (TTM) in a Neonate - A Case Report - Tamaria, Kailash Chand; Matlani, Monika; Meena, Shyam S. (Journal of Nepal Paediatric Society, 2019)
Transfusion-transmitted malaria in neonates is uncommon entity. Here we report a case of severe malaria in a term neonate after exchange transfusion successfully treated with intravenous artesunate.